Support for nurseries - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Paulin Fianou, the coordinator of 'Matthieu 7,8' group of ORJEDEC (BP 05, Kouvé Tabligbo, Togo), writes to ask for 'support for the group s work with nurseries of fruit, teak and other agroforestry trees.'